The Influence of the 5A Customer Path on Online Purchasing Decisions (Case Study: 3SECOND Kuningan) - Affan NurFadillah Zein; Wenda Surya Lugina; Jefry Romdony; Yono Maulana (Indonesian Journal of Business Analytics, 2025)
The purpose of this study is to analyze the influence of variables in the Customer Path 5A concept (Aware, Appeal, Ask, Act, and Advocate) on Online Purchasing Decision among users of 3SECOND products through multiple linear regression analysis. Quantitative research was used to collect data through the distribution of questionnaires. This study involved 150 respondents, selected using the Hair et al 2021 method (6x25) to take samples. Criteria relevant to the research objectives were used to select respondents. Data were collected using a questionnaire with a Likert scale (1–5). Based on the results of the study, it can be concluded that the 5A Customer Path (Aware, Appeal, Ask, Act, and Advocate) has a significant influence on the online purchasing decisions of 3SECOND products in Kuningan. Each stage in the 5A model plays a role in shaping perceptions, interest, interaction, purchasing decisions, and consumer loyalty to the 3SECOND brand.